Trade flows, carbon leakage, and the EU emissions trading system - Tero Kuusi; Maria Wang (The Research Institute of the Finnish Economy (ETLA), 2022)
The EU's Emission Trading Scheme (EU ETS) has been shown to have reduced emissions in the participating countries and industries since its adoption in 2005. However, there is less evidence on the shifting of production outside EU to avoid emission controls. We study this so-called carbon leakage with gravity analysis of international trade flows and carbon intensities of trade. We provide a simple theoretical framework and study its implications empirically. Our findings with the new OECD data indicate that carbon leakage has in fact occurred due to the EU ETS, resulting in higher CO2 intensity of imports to the EU, and lower CO2 intensity of exports from the EU. The evidence on the value of imports also shows some increases from nonparticipating countries due to the ETS. We find that our results are broadly consistent with the theory.
Keywords: J23; J24; O33; 330; Carbon leakage; EU ETS; Gravity model